Global Music as an Open Concept — A Weitzian Approach to the Meanings of the “Music of the World” - Milenković, Dušan (Res Facta Nova, 2025)
In this paper, I argue that there are advantages to understanding “global music” (also known as “world music”) as an open concept, following Morris Weitz’s seminal account on the open-ended nature of art, as well as Theodore Gracyk’s characterization of popular music as an open concept. In the first part of the paper, I delineate prevalent critiques directed towards global music (or world music – I will use both terms interchangeably throughout the paper), which I present by commenting on David Byrne’s well-known article I Hate World Music. Central to my discussion are the two most dominant contentions: purported vagueness in defining the meaning and scope of global music, and its alleged propagation of politically incorrect values by broadly categorizing it as “non-Western music”. By employing a Weitzian approach to open concept strategy, I show that a strict definition of the meaning and scope of global music is not an imperative for a nuanced understanding of it. Furthermore, I contend that the open-ended nature of the concept of global music can help in ruling out the perception that its supposed “non-Westernity” is an “essential property” of the genre.